LibraryOperation during COVID-19 Pandemic (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A library is considered as the 'heart' of an educational institution and it is thecentre of learning for primary to higher education system. Due to the COVID-19pandemic, the library operation has been restrained due to safety issues of the users andlibrary staffs. A questionnaire survey was carried out using Google Form virtual platformfrom the top administrators of the libraries spread over India. Around 138 responses werereceived during the survey. The survey data were collected in Google spreadsheet andstored in MS Excel platform for further analysis.The normal precaution measures such as social distancing, using sanitizer and face masketc. need to be followed during library operation. The use of face shield, head cover, PPEkit etc. may be provided for the front desk and security personnel. The return booksshould be sanitized through isolation, UVC box technique, and home delivery systemmay be used during the pandemic.The vast virtual resources and online classes etc. should be explored and may bechannelized to the users through libraries. The remote access of library and otherresources login password, remoteXs service, IP authentication etc. may be allowed tousers for reducing frequent visit to the library. The virtual resources can also be created atthe library by the faculty members of the university for their students and users. Onlineexamination and evaluation may be promoted by the libraries during the pandemicsituation.The library floor design may be revised to maintain space between the usersusing mobile reading table with acrylic separation bars, acrylic sneezeguards, desk separators, front desk barriers, cough screens etc. in the library.